Analisis Pengaruh Tingkat Suku Bunga, Produk Domestik Bruto dan Kurs Terhadap Inflasi di Indonesia - Fuji Astuty (Journal of Accounting and Finance (JACFIN), 2023)
The stability of a country’s economy is a measure of economic development in that country. In addition, inflation is a concern for the government. This study aims to analyze the effect of interest rates, Gross Domestic Product (GDP), and exchange rates on inflation in Indonesia from 2007 -2021. This research uses secondary data with data sources obtained from Bank Indonesia and the Central Bureau of Statistics. The data used is time series data from 2007 to 2021. This research uses the Ordinary Least Square (OLS) method. This analysis shows that the interest rate variable partially has a positive and insignificant effect on inflation in Indonesia. While partially the gross domestic product and exchange rate variables negatively and significantly affect inflation in Indonesia. Meanwhile, simultaneously it has a positive influence on inflation in Indonesia from 2007 -2021. The coefficient of determination (R2) results show that inflation can be explained by variations in interest rate variables, gross domestic product, and exchange rates of 73.18% while explained variations in other variables that are not in this study amounted to 26.82%.